Analisis Variasi Abu Sekam Padi sebagai Bahan Pengganti Sebagian Semen terhadap Kuat Tekan Beton SCC (Self Compacting Concrete) - I Wayan Suardita; Kasmat Saleh Nur; Barry Yusuf Labdul (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Self-Compacting Concrete (SCC) is a type of concrete that can self-compact without the need for mechanical vibration, exhibiting excellent flowability. Rice husk ash is a residue produced from the combustion of rice husk ash and contains a high amount of amorphous silica, making it suitable as a partial substitute for cement in concrete mixtures as well as a filler material. Therefore,the utilization of rice husk ash in SCC presents an attractive alternative, particularly in the context of enviromentally friendly and sustainable constuction. This research aimed to analyze the effect  of using rice husk ash as a partial replacement for cement on the characteriscs and compressive strength of SCC. As experimental method was employed by preparing test specimens with rice husk ash  variations of 0%, 7,5%, 10%, and 12,5% by weight of cement. Based on the results of SCC characteristic tests, all variations exhibited good flowability, viscosity, and segregation resistance. However, the 7,5% and 12,5% variations showed poor passing ability (category III). The highest compressive strength was achieved at a 10% variation, reaching 39,65 MPa, which represented a 31,04% increase compared to SCC without rice husk ash (30,19 MPa). The 7,5% and 12,5% variations increased the compressive strength by 24,08% (37,46 MPa) and 6,46% (32,14 MPa), respectively compared to the rice husk ash.